2023
DOI: 10.1002/hsr2.1131
|View full text |Cite
|
Sign up to set email alerts
|

The trend of normal vaginal delivery and cesarean sections before and after implementing the health system transformation plan based on ICD‐10 in the northeast of Iran: A cross‐sectional study

Abstract: Background and Aims: Concerning the growing rate of cesarean sections (CSs) worldwide, encouraging normal vaginal deliveries (NVDs) and mitigating CS rates is a necessity. This study investigated the status of delivery in hospitals affiliated with the Mashhad University of Medical Sciences (MUMS) before and after implementing health system transformation plan (HSTP).Methods: A cross-sectional study was conducted in 2017 in the obstetrics and gynecology ward in four MUMS teaching hospitals. Data were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, their level of awareness and exposure to telemedicine has been very limited, and they have demanded more education in this area. On the other hand, considering that recent studies involve the use of telemedicine in many medical and health care settings [34][35][36][37][38][39][40][41], it is clear that students and future health care professionals must be equipped with adequate skills and knowledge in the use and operation of telemedicine technologies. Hence, such results can emphasize the necessity of planning, training, and empowering more digital health literacy and telemedicine among paramedical science students as the main users of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…However, their level of awareness and exposure to telemedicine has been very limited, and they have demanded more education in this area. On the other hand, considering that recent studies involve the use of telemedicine in many medical and health care settings [34][35][36][37][38][39][40][41], it is clear that students and future health care professionals must be equipped with adequate skills and knowledge in the use and operation of telemedicine technologies. Hence, such results can emphasize the necessity of planning, training, and empowering more digital health literacy and telemedicine among paramedical science students as the main users of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest statistics available to the public, in Baharlou Hospital, there are approximately 350 births each month, comprising 38% CS [ 49 ]. While compared to the pre-pandemic period, the rate of CS increased during the COVID-19 pandemic [ 50 ], the high rate of CS in Iran has always been a challenge in the field of maternal health [ 51 ]. Although this study suggests a possible approach to reduce the number of CS, the rate of CS in this study, and overall in Iran [ 52 ] is still higher than the world health organization (WHO) recommendation (maximum of 15%) [ 53 ], and further research is needed to identify contributing factors to this high number of CS.…”
Section: Discussionmentioning
confidence: 99%
“…In general, many studies today support the increasing impact of telehealth services through technology [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]; Considering the positive result of using teleophthalmology in screening, monitoring, adherence to treatment and improving the clinical conditions of patients with various eye diseases and the lack of reporting of side effects in therapeutic and monitoring approaches based on telemedicine, it can be concluded that the use of telemedicine in eye disorders using high-quality equipment and using multiple technologies in combination cause maximum effect and efficiency. As a result, policy makers and planners in this field should work on maximizing the quality of tele-ophthalmology equipment.…”
Section: Discussionmentioning
confidence: 99%